Análisis comparativo del rendimiento térmico entre colectores solares de doble y simple flujo de movimiento del aire. - Ramos Ramos, Marco Patricio (2023)
As we do not have precise data on the efficiency of solar collectors with single and double flow of air movement, it was proposed in this project to carry out a comparative analysis of the Thermal Performance between said collectors, using temperature data obtained in experimental tests, in similar environmental and construction conditions; These data were taken for 11 consecutive hours on June 29, 2023, from 7:00 a.m. to 6:00 p.m. For this objective, a data collector module was used, to which twenty thermistors were connected distributed in strategic points of the collector to collect data on the Inlet, Internal and Outlet Temperature of the collector, as well as an anemometer located at the outlet of the collector. collector, for collecting forced air velocity data; Likewise, a blower was used to circulate air inside each collector. A meteorological station was also used, which allowed real-time data to be taken on the Environmental Temperature and Solar Radiation to which the collectors were exposed. Once the data was recorded, a comparative analysis of the Thermal Performance between the two collectors was carried out, concluding that the double flow collector can generate higher Outlet Temperatures, with 35.13°C being the Maximum Temperature recorded by the double flow collector. flow and 33.56°C recorded by the single flow collector. Likewise, an Average Thermal Performance of 51% and 27% was obtained from the double and single flow collectors respectively, with an average Solar Radiation of 461.76 W/m2 and Average Environmental Temperature of 15.53 °C.